Use of Edaphic Bioindicators to Mitigate Environmental Impact and Improve Agricultural Research and Training - Ana Cano-Ortiz; José Carlos Piñar Fuentes; Juan Peña-Martínez; Eusebio Cano (Soil Systems)
The world is currently experiencing unsustainable development, which poses significant risks to global society. In response, there is a growing advocacy for sustainable development across all sectors, driven by social resilience. This shift is fostering substantial socio-environmental tensions. However, the combined power of scientific research and social education has the potential to reverse this trend. Transitioning from an unsustainable territorial model to a sustainable one is both feasible and economically profitable. This transition can be achieved through knowledge of soil bioindicators, which provide valuable information about soil nutrient content. By understanding these indicators, nutrient inputs can be tailored, reducing or eliminating pollutants such as excessive fertilizers, herbicides, and pesticides. Training experts and raising social awareness through education on new research are essential steps in this process. For decades, it has been recognized that globalization, industrialization, and population growth have driven unsustainable development, leading to degraded agroecosystems. To address this issue, government institutions are promoting sustainability through ecological agriculture and CO2 reduction, both of which can be supported by the use of soil bioindicators.